Age‐specific function of α5β1 integrin in microglial migration during early colonization of the developing mouse cortex. Issue 7 (18th April 2017) - Smolders, Sophie Marie‐Thérèse; Swinnen, Nina; Kessels, Sofie; Arnauts, Kaline; Smolders, Silke; Le Bras, Barbara; Rigo, Jean‐Michel; Legendre, Pascal; Brône, Bert
Abstract: Microglia, the immune cells of the central nervous system, take part in brain development and homeostasis. They derive from primitive myeloid progenitors that originate in the yolk sac and colonize the brain mainly through intensive migration. During development, microglial migration speed declines which suggests that their interaction with the microenvironment changes. However, the matrix–cell interactions allowing dispersion within the parenchyma are unknown. Therefore, we aimed to better characterize the migration behavior and to assess the role of matrix–integrin interactions during microglial migration in the embryonic brain ex vivo . We focused on microglia–fibronectin interactions mediated through the fibronectin receptor α5β1 integrin because in vitro work indirectly suggested a role for this ligand–receptor pair. Using 2‐photon time‐lapse microscopy on acute ex vivo embryonic brain slices, we found that migration occurs in a saltatory pattern and is developmentally regulated. Most importantly, there is an age‐specific function of the α5β1 integrin during microglial cortex colonization. At embryonic day (E) 13.5, α5β1 facilitates migration while from E15.5, it inhibits migration. These results indicate a developmentally regulated function of α5β1 integrin in microglial migration during colonization of the embryonic brain. Main Points: α5β1 integrin regulates the migration of microglia during embryonic corticogenesis. A developmental switch of α5β1 integrin function occurs between E13.5 and E15.5 from promoting to inhibiting microglial migration.